Inferior Frontal Gyrus Activation Underlies the Perception of Emotions, While Precuneus Activation Underlies the Feeling of Emotions during Music Listening - Ken-ichi Tabei (Behavioural Neurology)
While music triggers many physiological and psychological reactions, the underlying neural basis of perceived and experienced emotions during music listening remains poorly understood. Therefore, using functional magnetic resonance imaging (fMRI), I conducted a comparative study of the different brain areas involved in perceiving and feeling emotions during music listening. I measured fMRI signals while participants assessed the emotional expression of music (perceived emotion) and their emotional responses to music (felt emotion). I found that cortical areas including the prefrontal, auditory, cingulate, and posterior parietal cortices were consistently activated by the perceived and felt emotional tasks. Moreover, activity in the inferior frontal gyrus increased more during the perceived emotion task than during a passive listening task. In addition, the precuneus showed greater activity during the felt emotion task than during a passive listening task. The findings reveal that the bilateral inferior frontal gyri and the precuneus are important areas for the perception of the emotional content of music as well as for the emotional response evoked in the listener. Furthermore, I propose that the precuneus, a brain region associated with self-representation, might be involved in assessing emotional responses.